PENGARUH ROA, CR, PERTUMBUHAN PERUSAHAAN, DAN KOMISARIS INDEPENDEN TERHADAP OPINI AUDIT - Herry Hanly (Fakultas Ekonomi Prodi Akuntansi, 2020)
The purpose of this study is to examine and analyze the effect of Return on Assets, Current Ratio, Company Growth, and the Board of Commissioners on the Audit Opinion of the consumer goods industry sector companies listed on the Indonesia Stock Exchange in 2016 - 2019. The research method is quantitative descriptive research. The population used is industrial companies listed on the IDX in 2016 - 2019, totaling 58 companies. Samples in this study were 16 companies selected with certain criteria. The statistical method used is logistic regression analysis with the help of the SPSS 20 program. The results show that Return on Assets has a significant effect on audit opinion. Meanwhile, Current Ratio, Company Growth, and the Board of Commissioners have no and insignificant effect on the audit opinion.